2009
DOI: 10.1002/ejic.200900570
|View full text |Cite
|
Sign up to set email alerts
|

16‐Electron (Arene)ruthenium Complexes with Superbasic Bis(imidazolin‐2‐imine) Ligands and Their Use in Catalytic Transfer Hydrogenation

Abstract: The ligands N,N′‐bis(1,3,4,5‐tetramethylimidazolin‐2‐ylidene)‐1,2‐ethanediamine (BLMe) and N,N′‐bis(1,3‐diisopropyl‐4,5‐dimethylimidazolin‐2‐ylidene)‐1,2‐ethanediamine(BLiPr) react with [(η5‐C5Me5)RuCl]4 to afford cationic 16‐electron half‐sandwich complexes [(η5‐C5Me5)Ru(BLR)]+ (R = Me, 3; R = iPr, 4), which resist coordination of the chloride counterion because of the strong electron‐donating ability of the diimine ligands. Upon reaction with [(η6‐C6H6)RuCl2]2 or [(η6‐C10H14)RuCl2]2, these ligands stabilize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
28
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 76 publications
3
28
0
Order By: Relevance
“…For example, in the field of biomimetic coordination chemistry, peralkylated bifunctional nitrogen ligands for Cu and Fe were designed, [3,4] and in the transfer hydrogenation of acetophenone, Mo and Ru complexes of these ligands demonstrated their catalytic potential. [5] Abstract: In this work we report on the syntheses and properties of several new Ni complexes featuring the chelating bisguanidines bis(tetramethylguanidino)benzene (btmgb), bis(tetramethylguanidino)naphthalene (btmgn), and bis(tetramethylguanidino)biphenyl (btmgbp) as ligands. All complexes were structurally characterized by single-crystal X-ray diffraction and quantum chemical calculations.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the field of biomimetic coordination chemistry, peralkylated bifunctional nitrogen ligands for Cu and Fe were designed, [3,4] and in the transfer hydrogenation of acetophenone, Mo and Ru complexes of these ligands demonstrated their catalytic potential. [5] Abstract: In this work we report on the syntheses and properties of several new Ni complexes featuring the chelating bisguanidines bis(tetramethylguanidino)benzene (btmgb), bis(tetramethylguanidino)naphthalene (btmgn), and bis(tetramethylguanidino)biphenyl (btmgbp) as ligands. All complexes were structurally characterized by single-crystal X-ray diffraction and quantum chemical calculations.…”
Section: Introductionmentioning
confidence: 99%
“…for the ring-opening polymerization of lactides and for the atom transfer radical polymerization of styrene [15,16]. Furthermore, it was shown that bis(imidazolin-2-imine) ligands (BL R ), which exhibit pronounced electron-donor properties, are able to stabilize coordinative unsaturated 16- [19]. In accord with the presence of 16-electron species in solution, reasonable activity was observed upon using these complexes as catalysts in the transfer hydrogenation of ketones.…”
Section: Introductionmentioning
confidence: 99%
“…The II -η 6 -p-cymene-diamine complexes [22] and organo-ruthenium(III) amidinates [23]. They are also considerably longer than those for half-sandwich ruthenium(II) bis(imidazolin-2-imine) complexes [17,19] and indicate that the ligands 3a and 3b display a weaker electron-releasing capability.…”
mentioning
confidence: 99%
See 2 more Smart Citations